Pengaruh Media Pembelajaran Terhadap Motivasi Belajar Bahasa Arab Siswa Madrasah Tsanawiyah - Wakhidati Nurrohmah Putri (LISANIA: Journal of Arabic Education and Literature, 2017)
AbstractThe efforts to increase learning motivation can be done by using instructional media. This study aims to find out the use of media and the effect of the use of instructional media towards motivation to learn Arabic. This is a descriptive quantitative research. The population in this study are 94 students of immersion class at State Islamic Junior High School (MTs N) Plupuh Sragen. All students become the sample in this study. The data is processed by using descriptive statistics and correlation test of Product Moment. Based on the hypothesis test, the magnitude of the correlation coefficient (r) is 0.4723 greater than 0.207 with significance level of 5%. It can be concluded that Ha that there is "the effect of the use of instructional media to learn Arabic student motivation" is accepted. The results inform that there is a significant effect of media learning towards student motivation, especially in learning Arabic.